Ascorbic acid enhanced ciprofloxacin degradation with nanoscale zero-valent copper activated molecular oxygen. (September 2021) - Zhang, Kejia; Deng, Jing; Chen, Yijing; Xu, Chengcheng; Ye, Cheng; Ling, Xiao; Li, Xueyan
Abstract: The remediation of water polluted by fluroquinolones antibiotics remains an important issue. Although zero-valent copper (ZVC) coupled with molecular oxygen can destruct refractory organic pollutants, the activation efficiency still needs to be further improved. In this study, the introduction of ascorbic acid (AA) in ZVC/air process maintained a high-concentration of Cu(Ⅰ), which can efficiently activate molecular oxygen to generate reactive oxygen species (ROSs). Superoxide radicals and hydroxyl radicals coexisted in nZVC/AA/air system. The former contributed to the yield of H2 O2 and also acted as a mediator for Cu(Ⅱ)/Cu(Ⅰ) redox cycles, the latter was the pivotal ROSs for ciprofloxacin (CIP) destruction. The CIP degradation decelerated through the addition of excessive nZVC and AA, and the optimum dosages of nZVC and AA were determined to be 0.2 g/L and 1 mM, respectively. The developed nZVC/AA/air process could efficiently operate in a relative broad pH range of 3.0–7.0, which was due to the fact that AA prevented the precipitation of copper ions in solution via forming stable chelates. The coexistence of Cl − severely retarded the CIP removal. According to the results of UPLC-MS/MS analysis and density functional theory calculations, the plausible degradation pathways including the decarboxylation, defluorination, hydroxylation and cleavage of C–C bond in piperazine ring were proposed. Graphical abstract: Image 1 Highlights: The introduction of AA in nZVC/air system greatly accelerated CIP degradation. AA maintained a high-concentration of Cu(Ⅰ), which efficiently activated molecular oxygen to generate ROSs. Hydroxyl radicals mainly contributed to CIP destruction, while superoxide radical functioned as the mediator for copper cycles. Several key affecting factors including ZVC dosage, AA concentration, solution pH and chlorine were examined. The transformation route of CIP in nZVC/AA/air system was put forward.